2003
DOI: 10.1007/s00441-003-0720-6
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against the PER protein of Drosophila label neurons in the optic lobe, central brain, and thoracic ganglia of the crickets Teleogryllus commodus and Teleogryllus oceanicus

Abstract: We describe labeling of neurons in the central nervous system of two cricket species, Teleogryllus commodus and T. oceanicus, with both mono- and polyclonal antibodies against the PER protein. Western blots reveal that the monoclonal antibodies recognize a single protein with a molecular weight of approximately 94 kDa, i.e., similar to that of the PER protein of the moth, Anterea pernii. Neurons and their processes are labeled both in the optic lobes and in the central brain. Processes occur in the accessory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 62 publications
1
25
0
Order By: Relevance
“…In turn, this suggests that PER may be rhythmically released from nerve terminals, as with many other insect peptide messenger molecules (reviewed by Vafopoulou and Steel, 2005a). PER has also been reported in classical neurohemal sites such as the corpora cardiaca (Frisch et al, 1996;Wise et al, 2002;Lupien et al, 2003;Závodská et al, 2003b;Sedahová et al, 2004), consistent with a potential role of PER as a classical hormone. In Rhodnius, PER is seen in the axons of the LNs in the aMe, in which neuronal interactions are very probable.…”
Section: Multifunctionality Of Per and Pdfmentioning
confidence: 78%
See 1 more Smart Citation
“…In turn, this suggests that PER may be rhythmically released from nerve terminals, as with many other insect peptide messenger molecules (reviewed by Vafopoulou and Steel, 2005a). PER has also been reported in classical neurohemal sites such as the corpora cardiaca (Frisch et al, 1996;Wise et al, 2002;Lupien et al, 2003;Závodská et al, 2003b;Sedahová et al, 2004), consistent with a potential role of PER as a classical hormone. In Rhodnius, PER is seen in the axons of the LNs in the aMe, in which neuronal interactions are very probable.…”
Section: Multifunctionality Of Per and Pdfmentioning
confidence: 78%
“…This function obviously requires the presence of these proteins within the nucleus at certain times each day. However, in most species studied, PER has not been detected within nuclei and has been confined to the cytoplasm (Sauman and Reppert, 1996;Závodská et al, 2003aZávodská et al, ,b, 2005Lupien et al, 2003;Sedahová et al, 2004;Shao et al, 2006;Wen and Lee, 2008). These studies used various different fixation and tissue preparation protocols, which suggests that the absence of nuclear PER was not a consequence of improper technique.…”
Section: Multifunctionality Of Per and Pdfmentioning
confidence: 90%
“…Findings supporting this hypothesis are that PDF and PERIOD often coexist not only in Drosophila but also in the cricket Teleogryllus commodus (Helfrich-Förster, 1995;Lupien et al, 2003), that flies lacking PDF often become arrhythmic in constant darkness (Renn et al, 1999), and that the restoration of rhythmic locomotor activity after transection of the Fig. 6.…”
Section: Functional Role Of Pdfmentioning
confidence: 85%
“…Results of immunostainings with anti-Periplaneta PER antibody in Periplaneta americana are not perfectly consistent with their view: PER-immunoreactivity was observed in two clusters of small sized cells located dorsal and ventral to the outer optic chiasma in addition to the neurons in the pars intercerebralis and pars lateralis in the central brain (Takeda et al, 2000). Recent findings in two cricket species Teleogryllus commodus and T. oceanics (Lupien et al, 2003) using antibodies against Drosophila PER might support their view, however. Anti-PER-immunoreactive neurons located near the medulla send dens tufts of small arborizations into the accessory medulla, processes to the medulla and the proximal lamina area, and project through the optic stalk.…”
Section: Locus Of the Clockmentioning
confidence: 93%
“…PER-immunostainings have revealed that in many insect species, several clusters of PER-immunoreactive neurons are located in the optic lobe as well as in the central brain (Lupien et al, 2003;Zavodska et al, 2003). Their number of clusters and localization vary from species to species.…”
Section: Locus Of the Clockmentioning
confidence: 99%